Transthoracic computed tomography-guided lung biopsy in the new era of personalized medicine. (18th March 2019) - Russo, Umberto; Sabatino, Vittorio; Nizzoli, Rita; Tiseo, Marcello; Cappabianca, Salvatore; Reginelli, Alfonso; Carrafiello, Gianpaolo; Brunese, Luca; De Filippo, Massimo
Computed tomography-guided lung biopsy is a valid and safe procedure for characterizing pulmonary nodules. In the past years, this technique has been mainly used to confirm the malignant nature of undetermined pulmonary lesions; however, today its role has been completely renewed. With the advent of target therapy and immunotherapy, it has arisen for lung cancer, in inoperable patients, the necessity to obtain adequate bioptical material to perform a correct molecular characterization of the lesion. Moreover, the possibility of acquired drug-resistance mechanisms makes it necessary in some cases to rebiopsy these lesions over time. For these reasons, it is likely that the request of computed tomography-guided lung biopsy will increase in the future, therefore every radiologist should be confident with its most important aspects.